Odpowiedzi

2009-06-06T18:34:08+02:00
Rozwiązanie zaraz będzie w załączniku
1 5 1
  • Użytkownik Zadane
2009-06-06T18:49:30+02:00
B)s= vt/:v
s/v=t

s=vt/:t
s/t=v

c)a=w2r
w2r=a/:r
w2/a/r /pierwiastkujemy
w= pierwiastek z a/r

a=w2r
w2r=a/:w2
r=a/w2

d)F=ma
ma=F/:m
a=F/m

F=ma
ma=F/:a
m=F/a

a)Ek= mV2/2 /*2
2Ek=mV2
mV2=2Ek/m
V2=2Ek/m / pierwiastkujemy
V= pierwiastek z 2Ek/m

Ek= mV2/2 /*2
2Ek=mV2
mV2=2Ek/V2
m= 2Ek/V2

e) s=at2/2 /*2
2s= at2
at2=2s/:t2
a=2s/t2

s=at2/2 /*2
2s= at2
at2=2s/:a
t2=2s/a / pierwiastkujemy
t= pierwiastek z 2s/a

f) T1/V1=T2/V2
T1*V2=V1*T2 /:T1
V2= V1*T2/T1

T1/V1=T2/V2
T1*V2=V1*T2
V1*T2=T1*V2/:V1
T2=T1*V2/V1

g) P=a2
a2=P/pierwiastkujemy
a = pierwiastek z P

h) L=2pi r
2pi r=L/: 2pi
r= L/2pi

i)P=pi r2
pi r2=P/:pi
r2=P/:pi / pierwiastkujemy
r= pierwiastek z P/pi
1 5 1